2010
DOI: 10.1093/rpd/ncq535
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model of single-strand annealing for the repair of DNA double-strand breaks

Abstract: Ionising radiation induces different types of DNA damage, including single-strand breaks, double-strand breaks (DSB) and base damages. DSB are considered to be the most critical lesion to be repaired. The three main competitive pathways in the repair of DSB are non-homologous end joining (NHEJ), homologous recombination (HR) and single-strand annealing (SSA). SSA is a non-conservative repair pathway requiring direct repeat sequences for the repair process. In this work, a biochemical kinetic model is presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 252 publications
(353 reference statements)
1
10
0
Order By: Relevance
“…The solutions of the equations provide individual protein activity kinetics and overall repair kinetics, and these can be compared with experimental measurements (usually rate of repair of DSBs, post-irradiation, using PFGE in the dose range of 40-100 Gy). While most of the models dealt with the NHEJ pathway (e.g., [41,42,44,49,63,64,[111][112][113][114], some have also considered single-strand annealing (SSA) [115]; microhomology-mediated end-joining (MMEJ) [48]; application to high LET radiations [48]; and base-excision-repair (BER) [46].…”
Section: Published Computational Modeling Studies Of Dsb Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions of the equations provide individual protein activity kinetics and overall repair kinetics, and these can be compared with experimental measurements (usually rate of repair of DSBs, post-irradiation, using PFGE in the dose range of 40-100 Gy). While most of the models dealt with the NHEJ pathway (e.g., [41,42,44,49,63,64,[111][112][113][114], some have also considered single-strand annealing (SSA) [115]; microhomology-mediated end-joining (MMEJ) [48]; application to high LET radiations [48]; and base-excision-repair (BER) [46].…”
Section: Published Computational Modeling Studies Of Dsb Repairmentioning
confidence: 99%
“…Taleei et al [115] published a study on the biochemical kinetic modeling of single strand annealing (SSA) for the repair of radiation-induced DSBs. Although this work was done earlier than that on NHEJ, the basic principles and modeling procedures were similar.…”
Section: Published Computational Modeling Studies Of Dsb Repairmentioning
confidence: 99%
“…Inspection of the interquartile range of the hyperparameters confirms that a combination of fast, slow and intermediate repair is sufficient to describe the wild type and mutant data, furthermore a two sided Kolmogorov Smirnov test between the posterior distributions for the hyperparameters confirmed that the four distributions were significantly different to one another Table 3: Median posterior parameter values with 0.5 credible regions. Values can be compared to initial binding rate constants from two models in the literature; k = 0.5 hrs −1 for NHEJ [50] and k = 0.057 hrs −1 for SSA [51]. Half times of DSBs can be calculated using t 1/2 = log e /K .…”
Section: Data Model Parameters Hyperparameters Fastmentioning
confidence: 99%
“…Mean parameter values and repair half times after ABC SMC. Values can be compared to initial binding rate constants from two models in the literature[55] and[56].…”
mentioning
confidence: 99%
“…While, at the time of the earlier paper (Sankaranarayanan and Wassom 2005), we did not have a genome-based model for specifically considering NHEJ, HRR and NAHR repair for predicting genetic risks associated with radiation exposure of males (spermatogonial irradiation), such a model is currently being developed (Taleei et al 2010a(Taleei et al , 2010b.…”
Section: Extension Of the Concepts Discussed In The First Section To mentioning
confidence: 99%